Vacuolar Processing Enzymes Modulating Susceptibility Response to Fusarium oxysporum f. sp. cubense Tropical Race 4 Infections in Banana - Wan Abdullah, Wan Muhamad Asrul Nizam; Saidi, Noor Baity; Yusof, Mohd Termizi; Wee, Chien-Yeong; Loh, Hwei-San; Ong-Abdullah, Janna; Lai, Kok-Song (Frontiers in Plant Science, 2022)
Fusarium oxysporum f. sp. cubense tropical race 4 (FocTR4) is a destructive necrotrophic fungal pathogen afflicting global banana production. The infection process involves activation of programmed cell death (PCD). Here, seven Musa acuminata vacuolar processing enzyme (MaVPE1-MaVPE7) genes associated with PCD were successfully identified. Phylogenetic analysis and tissue-specific expression categorized these MaVPEs into the seed and vegetative types. FocTR4 infection induced majority of the MaVPEs expression in the susceptible cultivar, ‘Berangan’ as compared to the resistant cultivar, ‘Jari Buaya’. Consistently, upon FocTR4 infection, high caspase-1 activity was detected in susceptible cultivar while low-level of caspase-1 activity was recorded in resistant cultivar. Inhibition of MaVPEs activity via caspase-1 inhibitor in susceptible cultivar reduced tonoplast rupture, decreased lesion formation, and enhanced stress tolerance against FocTR4 infection. Additionally, Arabidopsis VPE-null mutant exhibited higher tolerance to FocTR4 infection, indicated by reduced sporulation rate, low-level of H2O2 content, and high-level of cell viability. Comparative proteomic profiling analysis revealed an increase in the abundance of cysteine proteinase in the inoculated susceptible cultivar as opposed to cysteine proteinase inhibitors in the resistant cultivar. In conclusion, increased of VPE-mediated PCD serves crucial roles in modulating susceptibility response during compatible interaction, which facilitated FocTR4 colonization on the host.